Synthesis and Characterization of Oligomer 4-Vinylpyridine as A Corrosion Inhibitor for Mild Steel in CO2 Saturated Brine Solution - Ilim Ilim; Alan Jefferson; Wasinton Simanjuntak; Marc Jeannin; Yana Maolana Syah; Bunbun Bundjali; Buchari Buchari (Indonesian Journal of Chemistry, 2016)
In this work, the oligomer of 4-vinylpyridine designated as O(4-VP) was synthesized by hydrogen peroxide initiated chain growth polymerization and characterized in terms of molecular weight and structure by matrix assisted laser desorption ionization time of flight mass spectroscopy (MALDI-TOF MS). The oligomer was tested as corrosion inhibitor of mild steel in brine solution saturated with carbon dioxide, with the main purpose to investigate the effect of inhibitor concentrations and temperatures on the inhibition activity defined in terms of corrosion rate and percent of protection. The inhibition tests were carried out using the methods of weight loss (WL) and linear polarization (LP). Characterization using MALDI-TOF MS revealed that the oligomer has the mass (m/z) in the range 200-2400, which corresponds to chain length of 2-22 repeating units. The results of corrosion rate measurements show that the corrosion rate with the use of oligomer is significantly lower than that without inhibitor, demonstrating that the oligomer functioned as effective corrosion inhibitor, while the 4-vinyl pyridine monomer was found to promote the corrosion. It was also found that the protection by the oligomer increased with increasing temperature and it was predicted the oligomer was chemically adsorbed by the surface of the metal.